TEACHER-STUDENT INTERPERSONAL COMMUNICATION RELATIONSHIP AND STUDENT MOTIVATION LEVEL WITH STUDENT SELF-ESTEEM CLASS XII TKJ SMK TRIDAYA BEKASI - Nur Intan Hasanah; Hilda Meriyandah; Riris Oktryna Silitonga (Rena Cipta Mandiri, 2023)
The empathetic attitude of teachers who are willing to listen to students' complaints, suggestions and suggestions, provide opportunities for free thinking and opinions, will have an effect on realizing the success of the teaching and learning process, but this cannot be understood by students. Teachers always think optimistically about the abilities of students and believe that students are able to achieve the expected competencies, help students' difficulties, make students have motivation and enthusiasm to learn. This is where the importance of the role of the teacher's interpersonal communication skills on student learning motivation must be developed so that students do not always interact with their gadgets.This study aims to determine the relationship between teacher-student interpersonal communication and the level of student motivation with the self-esteem of Class XII TKJ SMK Tridaya Bekasi students.This study uses a descriptive analytic method with a quantitative nature and a cross sectional research design. The population in this study was 140 TKJ class XII students at Tridaya Sakti Vocational School with a total sample of 104 students who were taken using consecutive sampling.the research shows that there is a relationship between interpersonal communication and motivation with self-esteem of class XII students of TKJ SMK Tridaya Bekasi (P value = 0.000) which means there is a significant positive relationship between interpersonal communication and motivation with self-esteem of class XII students of TKJ SMK Tridaya Bekasi.after doing this research there is a relationship between teacher-student interpersonal communication and the level of teacher motivation with self-esteem in class XII TKJ SMK Tridaya Bekasi.